2021
DOI: 10.1017/s0022215121000712
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caloric test asymmetry on response to treatment in vestibular migraine

Abstract: Objective This study aimed to examine the association between caloric asymmetry and response to treatment in patients with vestibular migraine. Method Dizziness Handicap Inventory scores were compared between patients with less than and more than 25 per cent asymmetry (using Cohen effect size) in a cohort of definite vestibular migraine patients who underwent caloric testing between August 2016 and March 2019. Results A total of 31 patients (mean age: 48.7 ± 20.0 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition, while vestibular testing cannot identify the presence of VM, it can put in evidence a concurrent dysfunction such as uncompensated vestibular hypofunction (due to peripheral or central mechanisms), comorbid BPPV as well as utricular/saccular dysfunction ( 35 ). Additionally, certain patterns can emerge on testing as well and help guide the diagnosis and/or the treatment plan ( 36 ). For instance, motion sensitive individuals tend to have longer time decay constants on step velocity rotary chair testing ( 37 , 38 ).…”
Section: Care Gap 3: Lack Of a Known Diagnostic Laboratory Testing Or An Objective Marker Available For Cliniciansmentioning
confidence: 99%
“…In addition, while vestibular testing cannot identify the presence of VM, it can put in evidence a concurrent dysfunction such as uncompensated vestibular hypofunction (due to peripheral or central mechanisms), comorbid BPPV as well as utricular/saccular dysfunction ( 35 ). Additionally, certain patterns can emerge on testing as well and help guide the diagnosis and/or the treatment plan ( 36 ). For instance, motion sensitive individuals tend to have longer time decay constants on step velocity rotary chair testing ( 37 , 38 ).…”
Section: Care Gap 3: Lack Of a Known Diagnostic Laboratory Testing Or An Objective Marker Available For Cliniciansmentioning
confidence: 99%
“…For instance, Yilmaz et al observed caloric weakness in 34% and abnormal vHITs in 18% of vestibular migraine patients during interictal assessment [ 19 ], while Li et al described caloric weakness in 19.4% for acute episodes [ 24 ]. Caloric weakness is variable and has been described in up to 56% of patients with vestibular migraine [ 17 , 20 , 22 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%